Education and society: Themes, perspectives, practices - Thapan, Meenakshi (New York Oxford University Press, 2015)
This work provides an overview of the major underlying themes in the sociology of education. All essays are based on empirical research and, using an ethnographic approach, seek to understand education in India. The book discusses social issues and contexts that underpin education in India.
Keywords: Education--Social aspects--India